Impact of exercise-induced alterations on gut microbiota diversity and composition: comparing effects of different training modalities - Yihan Wang; Shuang Bai; Tiance Yang; Jianjun Guo; Xiaoming Zhu; Ying Dong (Cell Regeneration)
Abstract Exercise has been shown to influence gut microbiota composition, but the specific effects of different exercise modalities on microbial diversity remain unclear. Understanding these differences is essential for optimizing exercise programs to enhance both physical fitness and gut health. This study compared the gut microbiota profiles of participants undergoing moderate-intensity continuous training (MICT), high-intensity interval training (HIIT), and high-intensity functional training (HIFT) using 16S rRNA gene sequencing. Thirty-one previously untrained healthy university students were randomly assigned into MICT (n = 7), HIIT (n = 12) and HIFT (n = 12). The results revealed that distinct gut microbiome profiles in participants under different exercise modes. Notably, the alpha-diversity gradually increased from the MICT group to the HIFT group. In addition, there was a progressive shift towards a Faecalibacterium-dominated microbial type from HIIT to HIFT group compared to MICT group. Individuals in the HIFT group were identified to be enriched with Lactobacillus and Limosilactobacillus, along with reduced Actinomyces and Anaeromassilibacillus. Functionally, the KEGG pathway and enzyme analysis using PICRUST2 revealed that the HIFT group exhibited prominence in muscle function-related pathways and enzymes, specifically ko00280 (valine, leucine, and isoleucine degradation), as well as the enzyme EC: 3.4.11.14 (alanine aminopeptidase). In conclusion, these findings highlight how exercise modality influences gut microbial diversity, with HIFT promoting a more favorable microbial profile compared to traditional endurance training. Understanding these effects can help tailor exercise programs to improve both fitness and gut health.